Developing bus rapid transit - Ferbrache, F (Elsevier, 2018)
Writing on geographical development, James Sidaway (2012:49) asks "how useful is it to talk about the geography of development or of developing countries"? It is a topic that has been discussed at length by academics and practitioners in the field of development studies, yet reverberations seem not to have penetrated certain areas of transport studies despite links between transport, social mobility, poverty alleviation and international development (Hickman, 2014; Hickman et al., 2015; World Bank, 2002). This commentary is concerned with geographies of development conveyed in literature on bus rapid transit (BRT), a bus-based mode of urban transit that has been championed by academics such as Gilbert (2008) and Venter et al. (2018), and organisations such as the World Bank, 2002 ; World Bank, 2004 as a promising investment in poverty-oriented urban development strategies.